(untitled) (Asian Journal of Medical and Biological Research, 2016)
The present study was designed with a view to study the body weight and hematological parameters; total erythrocyte count, haemoglobin concentration, packed cell volume and erythrocyte sedimentation rate of growing broilers fed with standard poultry ration. Broilers were kept under close observation for a period of 14 days and body weight was measured at each 7 days interval up to the end of the 35 days of experimental period. A total of 20 (7 days old) broiler chicks were reared throughout the entire period of study. These chicks were randomly divided into four equal groups (n=5). Group A considered as control, fed only standard ration. Group B, C and D was considered as treated group. Group B with vitamin AD3E 1 ml/5 liter drinking water. Group C treated with mineral 1 ml/5 liter dirking water and Group D treated with vitamin (AD3E) 1 ml/5liter and mineral 1 ml/5 liter dirking water with standard ration. It was observed that body weight of broiler increased significantly (p<0.01) in group D compare to group A, B, & C. Total erythrocyte count, haemoglobin concentration and erythrocyte sedimentation rate values were significant (p<0.01) in the treated groups as compared to that of control group A. So it is concluded that vitamin (AD3E) and mineral supplementation with standard ration is beneficial for broiler production and economically profitable. Asian J. Med. Biol. Res. December 2015, 1(3): 487-494